BAURAN PEMASARAN BUAH DURIAN DI KAWASAN BOULEVARD MALL, KOTA MANADO - Revo Yefta Sumampow; Caroline B. D. Pakasi; Lyndon ., Pangemanan (AGRI-SOSIOEKONOMI, 2016)
The purpose of this study was to identify elements in "Marketing Mix 4P" which applies to the marketing of durian at Boulevard Mall, Manado. This research was carried out for 2 months from April to May 2016. Data was retrieved through a survey consisting of primary and secondary data. Data was collected using a "purposive sampling" method, intentionally interviewing six respondents from fifteen respondents in the area of Boulevard Mall, Manado. There are four types of durians sold in Boulevard Mall: durian gajah, durian susu, durian mentega, and durian madu. Prices are relatively affordable and vary based on the type, with the highest price being durian gajah. The sale location in Boulevard Mall was selected by the sellers because it is within easy reach of the southern part of Manado and has a lively atmosphere. It is close to the beach, which is an ideal setting for relaxing while enjoying durian. Sellers promote their goods to consumers by offering an opportunity to bid prices, giving bonuses when consumers buy a certain amount, offering delivery services, and giving consumers the opportunity to taste test it for free.